COMPARING WETLAND ECOLOGICAL LITERACY IN GEOGRAPHY STUDENTS: ONLINE AND OFFLINE LEARNING EFFECTIVENESS EVALUATION - Setiawan, Faisal Arif; Saputra, Aswin Nur; Sandy, Aisyah Trees; Huda, Rofi’ul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2024)
Education has undergone significant transformations in recent years, driven by rapid technological advancements and an increasing reliance on online learning platforms. This shift from traditional classroom settings to digital environments has presented challenges for both educators and students, potentially impacting students’ ecological literacy. This study examines the comparative effects of online and offline learning on wetland ecological literacy among geography education students. Using a quantitative research approach, it evaluates the average ecological literacy scores of two cohorts: the 2019 cohort, which engaged in offline learning (average score: 75), and the 2020 cohort, which participated in online learning (average score: 72). The Wetland Ecology Literacy Questionnaire, based on Anderson’s cognitive dimensions (factual, conceptual, procedural, and metacognitive), served as the primary assessment tool. The results indicate a statistically significant difference in ecological literacy between the two learning modalities, with offline students achieving an average score of 13.28 compared to 11.83 for online students. An independent t-test yielded a p-value of 0.002 (<0.05), confirming that offline learning is more effective in fostering ecological literacy. These findings suggest that traditional, in-person learning remains superior to online methods in enhancing students’ ecological literacy.